Building the Corporate’s Image and Reputation on Twitter - Arévalo Martínez, Rebeca Illiana (2014)
The communication between organizations and their stakeholders has evolved as the waves of competitive challenges that have marked technological innovations (Kanter, 2006). Since 2006 it has become necessary not only to increase interaction particularly via social media, but also to incorporate aspects of organizational responsibility and its foundations in values (Kotler, Kartajava, & Setiawan, 2011) which directly influence in building its image (Capriotti, 2009) and reputation (Villafañe, 2004). This article analyzes the image and reputation of some private organizations in Mexico through the study of the activity they have in this social media. The results of this research suggest some conclusions regarding the importance of strategy in the use of Twitter as a basis for building the reputation of the organizations which must recognize the communication as a two-way process that accounts for interaction processes and mutual influence over time.